Penggunaan Atrium pada Bangunan Rumah Sakit Bertingkat dan Pengaruhnya terhadap Keselamatan Jiwa terhadap Bahaya Kebakaran - Tambunan, Lily; Sudradjat, Iwan; Suprapto, Suprapto (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2020)
The use of atrium in hospital buildings accelerating the patient's healing process and reduce the impression of stress on hospital buildings. However, the presence of the atrium can also pose a fire hazard because it can be a means of spreading smoke quickly. This study determines the effect of atriums in hospital buildings on the level of life safety in the event of a fire. The study was conducted at two hospitals in Bandung and Jakarta, Indonesia. The level of life safety is assessed through the difference between the time needed for the evacuation, referred to as RSET, and the time taken by smoke to cause a critical condition for occupants, called ASET, where RSET must be shorter than ASET. The analysis carried out on two physical configurations: open and closed atrium, and the results of this study showed that with an open atrium, the smoke quickly covered the evacuation route before the evacuation process completed, or ASET<RSET. The fire room door must be closed, and the smoke-barrier must be installed around the atrium to prevent the spread of smoke into patient rooms, thus fulfill the ASET<RSET criteria.